Solar-thermochromism of a hybrid film of VO2 nanoparticles and CoII–Br–TMP complexes. Issue 71 (15th July 2016) - Zhu, J. T.; Huang, A. B.; Ma, H. B.; Bao, S. H.; Ji, S. D.; Jin, P.
Abstract : This work reports a VO2 /Co II –Br–TMP hybrid film with excellent optical performance and an evident temperature-dependent colour change. Abstract : A hybrid film consisting of VO2 nanoparticles and Co II –Br–TMP complexes was prepared. The Co II –Br–TMP complexes containing cobalt(ii ), trimethylolpropane (CH3 CH2 C(CH2 OH)3, TMP) and bromine were selected to be combined with VO2 nanoparticles for the first time. Evident colour-change behaviour in response to temperature change and enhanced optical performance of this composite were reported.